Soft chemical deposition of BiFeO3 multiferroic thin films - Gonzalez, A. H. M.; Simoes, A. Z.; Cavalcante, L. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Riccardi, C. S. (American Institute of Physics (AIP), 2007)
BiFeO3 thin films free of secondary phases were obtained by the soft chemical solution on Pt(111)/Ti/SiO2/Si substrates after annealing at 500 degrees C for 2 h. The film grown in the (100) direction presented a remanent polarization P-r of 31 mu C/cm(2) at room temperature. Electrical measurements using both quasistatic hysteresis and pulsed polarization confirm the existence of ferroelectricity with a switched polarization of 60-70 mu C/cm(2), Delta P=(P-*-P). Low leakage conduction and an out-of-plane piezoelectric (d(3)) coefficient of 40 pm/V were obtained by the improvement of preparation technology.